Problem mapping of the generation and treatment of forest biomass ashes in boiler Mapeamento dos problemas associados à geração e tratamento das cinzas na combustão da biomassa florestal em caldeira - Henne R.A. (2021)
© 2021, Universidade Federal de Santa Maria. All rights reserved.The nature of the problems associated with the biomass combustion in boilers and their impact on the performance of combustion equipment depends on the fuel’s characteristics, and the design and operation of the combustion equipment. Thus, the objective of this study was to map the problems associated with the generation and treatment of forest biomass ashes in an industrial boiler. The study was developed in a thermoelectric plant with a production of 28MW / hour originated from the combustion of residual forest biomass. Three biomass samples were collected before entering the boiler’s furnace and at four flowing points inside the boiler, where the treatment and recovery for the final disposal of the biomass ashes occur. To compare the collection points in the boiler and the biomass properties, part of the samples were calcined in the laboratory. The analysed properties were: inorganic elemental chemical composition; the ashes fusion test and the potentiality of occurrence of problems through the following indices: ash deposition (R); slag (Rs); inlay (Fu); viscosity (Sr) and alkali (Al). As for the elemental chemical composition, the compounds with the highest concentrations were silicon, aluminum, iron, calcium, potassium and magnesium oxides. The melting temperature of the ashes was between 1261 ° C and 1385 ° C at the collection points. The mapping of the problems indicated low risks of formation of slag and viscosity. The fouling index was high, from 0.69 for the decanter and 1.11 for the readler, the latter having a medium potential viscosity. The formation of alkali occurred in the readler and decanter, causing corrosion at these points. The calculations of the deposition rates, based on the elemental chemical composition of the ashes were able to express the problems that occur in the combustion of the forest biomass in the boiler.